Filmowe baśnie wyczerpane. Wpływ postmodernizmu na przeobrażenia filmowych adaptacji baśni produkcji Disneya - KWIATKOWSKA, ZUZANNA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Film fairy tales exhausted.The impact of postmodernism on the change in Disney film adaptations of fairy tales The author gives attention to the issue of modern adaptations of fairy tales produced by Walt Disney Animation Studios. The three selected films: The Princess and the Frog (2009), Tangled (2010) and Frozen (2013) show the changes taking place in the sphere of axiology and the aesthetics in animated fairy tale films under the influence of postmodern trends. She notes that the intertextual dialogue takes place not only at the literature-film level, but also between earlier and later adaptations. On the basis of this analysis, she tries to determine the type of viewer to whom the newly-created message is addressed.